Replication Checkpoint Protein Mrc1 Is Regulated by Rad3 and Tel1 in Fission Yeast - Zhao, Hui (American Society for Microbiology, 2003)
Fission yeast Mrc1 (mediator of replication checkpoint 1) is an adaptor checkpoint protein required for Rad3-dependent activation of the checkpoint kinase Cds1 in response to arrest of replication forks. Here we report studies on the regulation of Mrc1 by phosphorylation. Replication arrest induced by hydroxyurea (HU) induces Mrc1 phosphorylation that is detected by a change in Mrc1 electrophoretic mobility. Phosphorylation is maintained in cds1Δ, rad3Δ, and tel1Δ single mutants but eliminated in a rad3Δ tel1Δ double mutant. Mrc1 has two clusters of S/TQ motifs that are potential Rad3/Tel1 phosphorylation sites. Mutation of six S/TQ motifs in these two clusters strongly impairs Mrc1 phosphorylation. Two motifs located at S604 and T645 are vital for HU resistance. The T645A mutation strongly impairs a Cds1-Mrc1 yeast two-hybrid interaction that is dependent on a functional forkhead-associated (FHA) domain in Cds1, indicating that phosphorylation of T645 mediates Mrc1's association with Cds1. Consistent with this model, the T645 region of Mrc1 effectively substitutes for the T11 region of Cds1 that is thought to be phosphorylated by Rad3 and to mediate FHA-dependent oligomerization of Cds1. The S/TQ cluster that includes S604 is needed for Mrc1's increased association with chromatin in replication-arrested cells. These data indicate that Rad3 and Tel1 regulate Mrc1 through differential phosphorylation to control Cds1.